Land Reform and Child Health in the Kyrgyz Republic - Kosec, Katrina; Shemyakina, Olga N. (University of Chicago Press, 2024)
Can the establishment of private property rights to land improve child health and nutrition outcomes? We exploit a natural experiment in the Kyrgyz Republic following the collapse of socialism, whereby the government rapidly liquidated state and collective farms containing 75 percent of agricultural land and distributed it to individuals, providing 99-year transferable use rights. We use household surveys collected before, during, and after the privatization reform and spatial variation in its timing to identify its health and nutrition impacts. We find that young children aged 0-5 exposed to land privatization for longer periods of time accumulated significantly greater gains in height- and weight- for-age z-scores, both critical measures of long-term child health and nutrition. Health improvements appear to be driven by increases in consumption of home-produced food rather than increased income from sale of production, likely due to under-developed markets. We find minimal impacts on urban-dwelling children affected only indirectly by the reform.